2004
DOI: 10.1002/ijc.20515
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of the involvement of the Fas −670 promoter polymorphism in cervical cancer in situ

Abstract: Dear Sir,In a recent study in this journal of Chinese patients, Lai et al. 1 suggest that a single nucleotide polymorphism (SNP) at position Ϫ670 in the Fas receptor promoter is associated with development of cervical cancer, implying a possible effect of Fas-mediated apoptosis. We studied this candidate locus in 278 affected sib-pairs (ASPs) from Sweden with a diagnosis of cervical cancer by genotyping of the Fas SNP and calculation of maximum lod-score (MLS) values. The ASPs show no significant deviation fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 18 publications
2
21
0
1
Order By: Relevance
“…In addition, Zoodsma et al (2005) showed a relationship between FasR 670A ‡G and increased risk of adenocarcinoma and not squamous cell carcinoma of the cervix. However, in another study conducted in Chinese women, as well as in Caucasian populations, there was no association between Fas SNPs and cervical cancer susceptibility (Chen et al, 2013;Du et al, 2013;Engelmark et al, 2004b;Pavlidou et al, 2016;Sun et al, 2005) resonating with the findings from African populations (Table 3).…”
Section: Fas Cell Death Receptorsupporting
confidence: 48%
“…In addition, Zoodsma et al (2005) showed a relationship between FasR 670A ‡G and increased risk of adenocarcinoma and not squamous cell carcinoma of the cervix. However, in another study conducted in Chinese women, as well as in Caucasian populations, there was no association between Fas SNPs and cervical cancer susceptibility (Chen et al, 2013;Du et al, 2013;Engelmark et al, 2004b;Pavlidou et al, 2016;Sun et al, 2005) resonating with the findings from African populations (Table 3).…”
Section: Fas Cell Death Receptorsupporting
confidence: 48%
“…Zoosdma et al (13) have demonstrated that Fas-670 polymorphism might be involved in the development of adenocarcinoma of the cervix but not in the development of squamous cell carcinoma. Engelmark et al (21), Sun et al (11) and Chatterjee et al (18) did not show a significant association of the FAS/FASL polymorphisms with cervical cancer. Qiu et al (29) indicated that significantly increased risks in FAS-1377 AA carriers were found in the breast cancer subgroup but not in the lung cancer subgroup.…”
Section: Discussionmentioning
confidence: 92%
“…Although evidence of an association between FAS/FASL polymorphisms and cervical cancer risk has been reported, the findings remain controversial (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Therefore, we performed a meta-analysis of all published studies on the association between the FAS/FASL polymorphisms and cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However, the results of our case-control study did not support this hypothesis, presumably because not all gastric tumors express FAS as reported (positive cases up to 30% of gastric cancer) (Vollmers et al 1997;Osaki et al 2001). Based on previous epidemiological studies of the polymorphism, the positive and negative correlation between the polymorphism and a risk of cervical squamous cell carcinoma has been disregarded (Lai et al 2003;Engelmark et al 2004). Immunohistochemical analysis using pathological specimens would help to provide a biological explanation to resolve this discrepancy.…”
Section: Discussionmentioning
confidence: 99%